2016
DOI: 10.3389/fnbeh.2016.00195
|View full text |Cite
|
Sign up to set email alerts
|

Post-weaning Environmental Enrichment, But Not Chronic Maternal Isolation, Enhanced Ethanol Intake during Periadolescence and Early Adulthood

Abstract: This study analyzed ethanol intake in male and female Wistar rats exposed to maternal separation (MS) during infancy (postnatal days 1–21, PD1–21) and environmental enrichment (EE) during adolescence (PD 21–42). Previous work revealed that MS enhances ethanol consumption during adulthood. It is still unknown if a similar effect is found during adolescence. Several studies, in turn, have revealed that EE reverses stress experiences, and reduces ethanol consumption and reinforcement; although others reported gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
4
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 57 publications
2
21
4
2
Order By: Relevance
“…From the main results of this study, it can be concluded that, while treatment with BZP during adolescence led to higher anxiety at older ages, this was more typical of rats housed in enriched rather than in standard cages thereby suggesting that enrichment had enhanced the anxiogenic action of the drug. So contrary to expectations, enrichment did not appear to have provided protection from the development of BZP‐related higher anxiety reported previously (Aitchison and Hughes, 2006) similar to reports of increased voluntary ethanol consumption in rats (Berardo et al, 2016; Rockman et al, 1989). The possibility that enrichment may in some situations be detrimental rather than beneficial is not consistent with most of the literature and, as suggested by van Praag et al (2000), requires further investigation.…”
Section: Discussioncontrasting
confidence: 95%
See 3 more Smart Citations
“…From the main results of this study, it can be concluded that, while treatment with BZP during adolescence led to higher anxiety at older ages, this was more typical of rats housed in enriched rather than in standard cages thereby suggesting that enrichment had enhanced the anxiogenic action of the drug. So contrary to expectations, enrichment did not appear to have provided protection from the development of BZP‐related higher anxiety reported previously (Aitchison and Hughes, 2006) similar to reports of increased voluntary ethanol consumption in rats (Berardo et al, 2016; Rockman et al, 1989). The possibility that enrichment may in some situations be detrimental rather than beneficial is not consistent with most of the literature and, as suggested by van Praag et al (2000), requires further investigation.…”
Section: Discussioncontrasting
confidence: 95%
“…It is also inconsistent with reductions in the reinforcing value and thus addiction potential of other drugs such as heroin (El Rawas et al, 2009), cocaine (Solinas et al, 2008) and ethanol (Holgate et al, 2017). However, there are also examples of enrichment having the opposite effect such as increasing ethanol's reinforcing value (Berardo et al, 2016) thereby detracting from any perceived beneficial quality of the manipulation. It is accordingly possible that, in the present study, enrichment was similarly detrimental with respect to the action of BZP during adolescence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These traits have been long considered phenotypes associated with propensity for ethanol intake. We have recently observed, for instance, that rats selectively bred for high ethanol intake during adolescence significantly avoided the white, potentially dangerous, chamber of a light-dark box (Fernandez et al, 2017); and in other study, we found that male rats reared under environmental enrichment exhibited both enhanced ethanol intake and behaviors indicative of greater risk-taking, when compared to counterparts reared under standard conditions (Berardo, Fabio, & Pautassi, 2016). In the present study, however, the patterns of exploration of the light-dark box were similar in AMPH, MPH, and vehicle-treated rats.…”
Section: Discussionsupporting
confidence: 51%